Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.30699/jambs.27.120.14
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Hemodynamic Effects of Nebulized Dexmedetomidine and Nebulized Lidocaine in Children undergoing Fiberoptic Bronchoscopy

Abstract: Background & Objective: Several studies have shown that topical and intravenous Dexmedetomidine and Lidocaine can decrease pain and reduce consumption of analgesic drugs. However, Lidocaine may be accompanied with several side effects such as respiratory suppression, seizure, and cardiac arrhythmias. On the other hand, Dexmedetomidine has favorable properties such as low risk of apnea, analgesia, sympatholysis, and sedation. Therefore, the aim of this study was to compare the effects of nebulized Dexmedetomidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Dexmedetomidine loading dose was 1 µg/kg in five studies [ 22 , 23 , 27 , 28 , 29 ], 0.5 µg/kg in three studies [ 24 , 30 , 31 ], and 2 µg/kg in one study [ 32 ]. The included studies of dexmedetomidine were administered intravenously, with the exception of one study [ 32 ], which was administered by aerosol. The basic characteristics of the included studies are listed in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Dexmedetomidine loading dose was 1 µg/kg in five studies [ 22 , 23 , 27 , 28 , 29 ], 0.5 µg/kg in three studies [ 24 , 30 , 31 ], and 2 µg/kg in one study [ 32 ]. The included studies of dexmedetomidine were administered intravenously, with the exception of one study [ 32 ], which was administered by aerosol. The basic characteristics of the included studies are listed in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…All the studies demonstrated a low risk in terms of random sequence generation, incomplete outcome data, and selective reporting. For a small number of studies with assigned sequence hidden [ 22 , 29 , 32 ], subjects and researchers blinded [ 22 ], and blinded outcome measures, the researchers were unable to assess the risk [ 27 , 29 , 32 ]. Only one study because of allocation concealment, subjects, and operators’ implementation blindness was unclear, and the outcome measures were assessed by the operators, so the results are high risk [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations